1935
DOI: 10.1111/j.1469-185x.1935.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dermatophytes

Abstract: Summary. The dermatophytes are a group of fungi which parasitise animals by invading the keratinised portions of the epidermis. They appear to be unable to attack internal organs and are apparently dermatotropic. Ringworm in its various forms is a primary localised dermatophyte infection. The concept of the activity of the dermatophytes has been enlarged by the recognition that they can also determine secondary non‐parasitic skin lesions on distant parts of the body. Several records of isolations of these fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1937
1937
1981
1981

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It is common in diseases where there is a persistence of living organisms in the bloodstream [6]. Live fungi have been demonstrated in the bloodstream following inoculation, and during the course of dermatophytic infections [5,11]. Both Jadassohn [7] and Sulzberger [12] have shown that such fungi can remain viable in organs and body fluids for long periods of time and retain their potential pathogenicity for the skin.…”
Section: Discussionmentioning
confidence: 99%
“…It is common in diseases where there is a persistence of living organisms in the bloodstream [6]. Live fungi have been demonstrated in the bloodstream following inoculation, and during the course of dermatophytic infections [5,11]. Both Jadassohn [7] and Sulzberger [12] have shown that such fungi can remain viable in organs and body fluids for long periods of time and retain their potential pathogenicity for the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The older reviews include those by Tate (1929a,b) and Gregory (1935) and more recently Vanbreuseghem (1961), Grin and Ozegovic (1963), Hildick-Smith et al (1964), Balabanoff (1965), Ajello (1974), and .…”
Section: Dermatophytesmentioning
confidence: 98%
“…Gregory (1935) reviewed several of these cases which included patients with tinea capitis, favus, and tinea pedis due to several dermatophyte species. Sulzberger (1928) showed that following cutaneous inoculation of guinea pigs with A. quinckeanum (= M. or T. quinckeanum), the fungus could be cultured from blood for 2 days.…”
Section: Natural Infectionsmentioning
confidence: 99%
“…The above description is taken from Gregory (1935) and Rev. This species differs from E. deflexa in possessing septate spines.…”
Section: A Candidusmentioning
confidence: 99%